Four new species of the planthopper genus Catonidia Uhler, 1896 from China (Hemiptera: Fulgoromorpha: Achilidae) - Lv, Sha-Sha; Long, Jian-Kun; Yang, Lin; Chen, Xiang-Sheng (European Journal of Taxonomy, 2024)
Four new species of the genus Catonidia Uhler, 1896, C. triangula sp. nov., C. saccata sp. nov., C. trilobata sp. nov. and C. uncinata sp. nov. from China (Fujian, Guizhou, Yunnan and Hainan provinces), are described and illustrated, giving the genus 14 species in total. A checklist and key to all known species of Catonidia are provided, as well as a map of their geographic distributions.